ARTIFICIAL INTELLIGENCE IN EDUCATION: ASSISTANT OR COMPETITOR FOR TEACHERS - Xolmatova Sarvinoz Berdiyor qizi; Miraxmedova Asilaxon Lazizjon qizi; Alimkhanova Nigorakhon Amilevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This thesis explores the rapid usage of AI in education and its influence on teachers and students, analyzing whether it can serve as an assistant to make tasks easier and learning process more productive or can pose a threat to their jobs. Artificial Intelligence is a very beneficial tool for teachers to check the homework and to come up with creative activities and prepare fun games and videos to make the lessons much more interactive, making much more free time to prepare hand-outs or activities beforehand. Since technology has become developed every student has a great interest in AI-powered tools, not using them and engaging them during lessons would lead teacher to organize very mundane traditional classes. This thesis concludes that although AI tools are highly important and beneficial for education, they cannot fully replace human teachers because of the lack of human factors such as emphasis, emotion and endless kindness.